Long wire length of midimew-connected mesh network - Rahman, M.M. Hafizur; Mohd. Nor, Rizal; Awal, Md. Rabiul; Tengku Sembok, Tengku Mohd; Miura, Yasuyuki (Springer International Publishing, 2016)
Minimal DIstance MEsh with Wrap-around links (Midimew) connected Mesh Network (MMN) is a hierarchical interconnection network consists of several Basic Modules (BM), where the BM is a 2D-mesh network and the higher level network is a midimew network. In this paper, we present the architecture of MMN and evaluate the number of long wires, length of a long wire, and the total length for the long wire of MMN, TESH, and torus networks. It is shown that the proposed MMN possesses simple structure and moderate wire length. The long wire length of MMN is slightly higher than TESH network and far lower than that of 2D torus network. Overall performance suggests that, MMN is a good choice for future generation massively parallel computers.